Wrath of Poseidon [large type] - Cussler, Clive; Burcell, Robin (Cussler, Clive. Fargo adventures., 2020)
"Husband-and-wife team Sam and Remi Fargo come up against an old enemy while searching for a treasure that has been lost for centuries in this exciting adventure in the bestselling series by the Clive Cussler, Grand Master of Adventure"--